The Effect of Using Video on Students’ Speaking Skill Through Whatsapp Application at SMA Negeri 1 Kabangka - Setiawan, Budi; Suhartini, Lelly (Universitas Halu Oleo, 2021)
This study aims to find out whether there is a significant effect of using video on students’ speaking skill through WhatsApp Application at SMA Negeri 1 Kabangka. The design of study was pre-experimental design that consisted of one group pretest and post-test. Post-test was given to know students’ speaking skill after the treatment by using video through WhatsApp Application. The population of this study was all the second semester students of SMA Negeri 1 Kabangka who were registered in academic year 2018/2019. The sample of this study was one class namely IPA-3 which consisted of 22 students. The instrument of this study was oral test, the students told their most interesting experience about their holiday in the past. This study used paired samples t-test to analyze the result of the study after the data were normally distributed. The result showed that there was a significant effect of using video on students speaking skill through WhatsApp Application at SMA Negeri 1 Kabangka. It could be seen from the mean score of post-test was 2.5, while the mean score of pre-test was 1.82. In order to prove the hypothesis, the researcher took the conclusion by comparing between the value of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. So, it can be concluded that the value of Sig (2 tailed) was lower than the significance α value (0.000 < 0.05). In other words, (H1) was accepted. It means that there is a significant effect of using video on students speaking skill through WhatsApp Application at SMA Negeri 1 Kabangka and it can improve student’s speaking accuracy and fluency.